Utilization Pattern of Information Communication Technologies (ICTs) among Farmers of District Kannauj in Uttar Pradesh - Yagya Dev Mishra and Reeta Mishra, (Indian Journal of Extension Education, 2016)
The research study was conducted in 11 villages of district Kannauj in central Uttar Pradesh. Asurvey was done among aselected sample of 126 farmers with the help of an interview schedule. The farmers were asked questions regarding theirusage pattern of various ICT tools. The findings of the study reveal that a sizeable number of farmers possess mobilephones, radio and television at home. Few farmers also have access to the computer and internet through the youngermembers of their family. The mass media (both radio and television) is popularly used for news and entertainment. Afewrespondents used to watch/listen agricultural programmes on TV/radio. It is important to note that a sizable number offarmers are aware of the SMS services being offered by the KVK and other departments for agricultural related advice.The computer and internet access was found to be in infantry stage in the villages, but farmers were aware that in futureeach and every problem can be solved through computer. The frequent interruption in power supply, difficulty in technicalcontent, odd timings of broadcasting/telecasting are the major causes stated by the farmers for low popularity ofbroadcasting media. Radio remains a popular medium for weather and market related information. The older farmersfacing limitations of language and technological barriers in operating mobile and internet.